2022
DOI: 10.1007/s40519-022-01398-3
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of two weight stigma scales in Malaysian university students: weight self-stigma questionnaire and perceived weight stigma scale

Abstract: Background This study aimed to examine the psychometric properties of the Weight Self-Stigma Questionnaire (WSSQ) and Perceived Weight Stigma Scale (PWS) among Malaysian university students. Methods University students who were studying in a Malaysia university with a mean age of 24.0 years (n = 380; females 71.6%) were recruited through convenience sampling between 19 August and 30 September 2021. They completed a Google Form consisting of information on sociodemographic background, weight stigma, psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 42 publications
8
18
2
Order By: Relevance
“…In addition, our results also show a pattern of sociodemographic characteristics among postpartum women in China who internalize weight bias. Similar to previous studies [ 33 , 35 , 41 , 42 ], our study found BMI to be positively associated with WBI. WBIS scores were higher in overweight (M = 30.57) and obese (M = 31.75) postpartum women compared to those who were underweight (M = 15.83) or normal weight (M = 23.30).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, our results also show a pattern of sociodemographic characteristics among postpartum women in China who internalize weight bias. Similar to previous studies [ 33 , 35 , 41 , 42 ], our study found BMI to be positively associated with WBI. WBIS scores were higher in overweight (M = 30.57) and obese (M = 31.75) postpartum women compared to those who were underweight (M = 15.83) or normal weight (M = 23.30).…”
Section: Discussionsupporting
confidence: 91%
“…The PWSQ [33,34] contains 10 items (e.g., "You are treated with less respect than others") utilizing dichotomous scoring (0 = no; 1 = yes). The scores (ranging from 0 to 10) are summed and a higher score indicates a higher level of perceived weight stigma.…”
Section: Perceived Weight Stigma Questionnaire (Pwsq)mentioning
confidence: 99%
“…and modern test theory approaches (e.g., 2PL model, Rasch model, etc.) (19)(20)(21)(22) to demonstrate the validity and reliability of the Malay SAVE-6 Scale. CTT is commonly used approach to assess psychometric properties of a test.…”
Section: Introductionmentioning
confidence: 99%